Molecular Mechanisms of Sechium edule Based on Network Pharmacology and Molecular Docking on Hypertension - Rahmat Santoso; Kintoko; Nining Sugihartini (Jurnal Penelitian Pendidikan IPA, 2026)
Chayote is a fruit that has been used for centuries to treat various diseases, including hypertension. However, how the chemical compounds derived from chayote work in treating hypertension remains unclear. Integrating molecular docking and network pharmacology to elucidate the active constituents and potential mechanisms of chayote in treating hypertension. Initially, 50 active compounds from chayote and 97 key targets related to hypertension were identified through network pharmacology analysis. Then, the results of molecular docking and simulations showed: gibberellin A4; gibberellin A7; gibberellin A29; gibberellin A38; gibberellin A44; stigmasta-3,5-dien-7-one; stigmasterol and routinely overcome hypertension through the regulation of ACE, AKT1, ALB, SRC, and TNF genes. These compounds and genes may be key factors of chayote fruit in treating hypertension. Pathway enrichment analysis showed that the antihypertensive effect of chayote is regulated by the gibberellin A7 and TNF signaling pathways. These pathways are primarily associated with anti-oxidative stress, anti-inflammatory responses, and β-cell protection. This study identified the active constituents and potential signaling pathways involved in the antihypertensive effect of chayote. Result: These findings provide a theoretical basis for understanding the mechanism of the antihypertensive effect of chayote. Furthermore, this study may help develop health supplements or natural antihypertensive drugs based on chayote.